Kultura współpracy w szkole w percepcji nauczycieli szkół gimnazjalnych - Tłuściak-Deliowska, Aleksandra; Dernowska, Urszula (Studia Edukacyjne, 2020)
School culture, more than any other single factor, determines the ultimate success or failure of any school. Undoubtedly, it is one of the indicators of school quality as well as a multifaceted concept composed of many factors. The article presents the results of the pilot study which was aimed to determine the perception of collaborative school culture by the teachers. The research was administered to middle schools’ teachers in the regions of Podkarpacie and Mazovia. The quantitative research perspective was used to obtain data to validate factors such as: unity of purpose, collaborative leadership, professional development, teacher collaboration, collegial support, and learning partnership. The Polish version of the School Culture Survey inventory (S. Gruenert, J. Valentine, 1998) was used. The results implied that teachers and school principals generally value and contribute to creating a collaborative school culture, but still do not pay as much attention as necessary to create learning partnership with parents.